Synthesis and Evaluation of Derivatives of the Proteasome Deubiquitinase Inhibitor b‐AP15. (27th May 2015) - Wang, Xin; D'Arcy, Pádraig; Caulfield, Thomas R.; Paulus, Aneel; Chitta, Kasyapa; Mohanty, Chitralekha; Gullbo, Joachim; Chanan‐Khan, Asher; Linder, Stig
Abstract : The ubiquitin–proteasome system (UPS) is increasingly recognized as a therapeutic target for the development of anticancer therapies. The success of the 20S proteasome core particle (20S CP) inhibitor bortezomib in the clinical management of multiple myeloma has raised the possibility of identifying other UPS components for therapeutic intervention. We previously identified the small molecule b‐AP15 as an inhibitor of 19S proteasome deubiquitinase (DUB) activity. Building upon our previous data, we performed a structure–activity relationship (SAR) study on b‐AP15 and identified VLX1570 as an analog with promising properties, including enhanced potency and improved solubility in aqueous solution. In silico modeling was consistent with interaction of VLX1570 with key cysteine residues located at the active sites of the proteasome DUBs USP14 and UCHL5. VLX1570 was found to inhibit proteasome deubiquitinase activity in vitro in a manner consistent with competitive inhibition. Furthermore, using active‐site‐directed probes, VLX1570 also inhibited proteasome DUB activity in exposed cells. Importantly, VLX1570 did not show inhibitory activity on a panel of recombinant non‐proteasome DUBs, on recombinant kinases, or on caspase‐3 activity, suggesting that VLX1570 is not an overtly reactive general enzyme inhibitor. Taken together, our data shows the chemical and biological properties of VLX1570 as an optimized proteasome DUB inhibitor. Abstract : The compound b‐AP15 was previously shown to inhibit proteasome DUB (deubiquitinase) activity, leading to proteasome blocking and tumor cell apoptosis. The authors have examined the biological activities of a number of structurally related compounds and describe the analogue VLX1570. This compound is an inhibitor of proteasome DUBs USP14 and UCHL5, whereas other DUBs are not significantly inhibited.